Fulfillment Research Resources through Access Financial Report of Go Public Company at Library STIE Perbanas Surabaya Perpustakaan STIE Perbanas Surabaya - Bestari, Melati Purba (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2016)
Modern libraries are characterized by the diversity of information services to users, including to fulfill the information needs of researchers. Fulfill the information requirements for this research group is very important because the information provided affect the quality of research. Library of STIE Perbanas Surabaya efforts to fulfill the information needs of researchers is to provide research resources through the provision of access annual and financial report for go public company. To provide convenience to users who do research and need annual and financial report for go public, library of STIE Perbanas Surabaya provide easy access through online catalog. To fulfill the annual and financial report for go public company, library tracking data on Indonesian stock exchange and go public company. Library attempts to provide easy access to information is expected to support a process that requires researchers andÂ annual and financial report data so as to improve the quality and quantity of scientific works in the field of economics science, especially for subject of banking, finance and business.Â